Pédagogie immersive expérientielle : aborder les loisirs inclusifs et thérapeutiques en interagissant avec des personnes résidant dans un foyer de soins - Zaiane-Ghalia, Selma; Benimmas, Aïcha (Canadian Journal of Education/Revue canadienne de l'éducation, 2023)
In order to make students aware of the reality of people with special needs during inclusive recreation activities, this study experiments with experiential immersive pedagogy to arouse the curiosity and interest of future recreologists enrolled in the “inclusive recreation” course. Learners were immersed in the reality of a nursing home resident. The contact was articulated around a leisure activity based on painting, self-expression, and group exchange with the support of a painter. Twenty-seven students experienced immersive experiential learning in an atmosphere of respect and empathy. Qualitative analysis of experience narratives, evaluation questionnaires and direct observation notes demonstrates the formative impact of the immersive experiential pedagogical approach. Indeed, the results reveal the initial apprehensions related to the stereotypes conveyed in relation to mental health and the effect of the encounters and human interactions that helped to challenge them.